2017
DOI: 10.4236/ajac.2017.81001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Low Molecular Weight Thiol Composition in a Metastatic Prostate Cancer Cell Line (LNCaP) by LC-UV-MS and NMR after Labelling with the Ellman Reagent

Abstract: The low molecular weight thiols present in the deproteinized extract of a prostate cancer cell line (LNCaP-FGC) were analysed after derivatization with the Ellman reagent (ESSE). The mixed disulphides formed (RSSE) were fractionated, characterized and quantified by liquid chromatography on a C-18 column using UV detection. This revealed the presence, in femtomoles per cell, of glutathione (8.30 ± 0.73), cysteine (2.71 ± 0.04) and cysteinylglycine (0.83 ± 0.10), accounting for the bulk of the thiol present. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The thiol contents determined using the Ellman reagent on the cellular fractions obtained in the present (as shown in Figure 2) and previous studies [6,7] are given in Table 1 below. In earlier studies, the G15 protein thiol concentration was calculated from the adduct obtained from the Ellman reagent.…”
Section: Thiol Contents Of Cellular Fractionsmentioning
confidence: 80%
See 1 more Smart Citation
“…The thiol contents determined using the Ellman reagent on the cellular fractions obtained in the present (as shown in Figure 2) and previous studies [6,7] are given in Table 1 below. In earlier studies, the G15 protein thiol concentration was calculated from the adduct obtained from the Ellman reagent.…”
Section: Thiol Contents Of Cellular Fractionsmentioning
confidence: 80%
“…Recent work on a human prostate cancer cells, a lymph node line known as LNCaP, has shown that thiols other than GSH are present in the deproteinized extract (acid soluble fraction -ASF) of these cells [5,6]. Following up this work, investigations have focused on the protein thiol content of the chromatin cellular pellet left after removal of the ASF which was found to contain 76.7% of the cellular thiol (43.2 + − 2.9 fmol/cell).…”
Section: Introductionmentioning
confidence: 99%